Emerging Olive Anthracnose Pathosystem in Morocco - Khadija Benamar; Saad Benamar (Plant Health Cases, 2026)
Abstract Olive anthracnose, caused by various fungal species belonging to the genus Colletotrichum , is one of the most damaging diseases for olive cultivation in the Mediterranean area. Although the disease has been investigated widely in southern Europe, information regarding its epidemiology, pathogen diversity, and prevalence in North Africa is scarce. In Morocco, olive anthracnose has been considered a sporadic or secondary disease. However, it is becoming more prevalent due to climate variability, orchard intensification, and the wide cultivation of susceptible cultivars. The present case focuses on olive anthracnose in Moroccan olive cultivation. Moreover, disease epidemiology, host susceptibility, current management strategies practised to date, and key research challenges are highlighted. Furthermore, surveillance pillars, risk assessment strategies, and the establishment of sustainable climate-resilient management approaches adapted to the Mediterranean basin and North Africa are also presented. Information © The Authors 2026